Willingness to Pay of Ecotourism Visitors - Paranata, Ade; Sutanto, Himawan; Dakwah, Muhammad Mujahid (JEJAK: Jurnal Ekonomi dan Kebijakan, 2017)
This study aims at analyzing the willingness to pay (WTP) of the visitors in Bird Watching Ecotourism in Lake Meno and the factors that influence the WTP value. The research is located in Gili Meno. The method used is quantitative method. The total samples are 38 obtained by accidental sampling. The procedure of analysis used the Contingent Valuation Method and Logit Model. The results showed that in the samples there are 27 people (77.14%) who are willing to pay (dominated by foreign tourists) and eight people (22.86%) who are not willing to pay with various reasons. The average value of WTP that can be proposed as a reference of environmental service is Rp 39,189.